Integración del dividendo con la renta corporativa - De la Vega Rengifo, Beatriz (2020)
The objective of this paper is to demonstrate the relevance of the tax regime that taxes dividends as a factor that affects the investmentclimate of the country, regarding the constant evolution in their regulation and corporate income. In this sense, we will analyze the fiscal policy regarding the taxability of dividends, the critical aspects of the current regulation, and the international tax planning that can be developed based on the agreements to avoid double taxation signed by Peru.